China and the future global food situation - Huang, Jikun; Rozelle, Scott; Rosegrant, Mark W. (International Food Policy Research Institute, 1995)
The future of China's grain economy has been the subject of much debate. Some observers predict rapidly increasing grain imports that will strain the world's productive capacity. Most of China's own economists disagree: researchers in the Chinese Academy of Agricultural Sciences have long predicted and still believe the nation will remain at least self-sufficient. Whatever course China's grain economy takes, the stakes are high for China's own development and for the stability and health of the world's agricultural trade. This brief examines alternatives for China's grain production, consumption, and net trade, taking into account underlying structural factors.